Preference for vehicle ownership and use in Malaysia - Mohamad, J. (2008)
Using a household survey dataset in Klang Vally area this paper examines the characteristics of households on vehicle ownership, vehicle type choice, and vehicle usage rates in the Kuala Lumpur region and it’s surrounding. The results have clearly show that households in Malaysia tend to have more vehicles where their wealth is better, while the trend of motorcycle ownership shows an opposite behavior. The analysis has shows that motorcycle is much preferred by the households who have a lower salary. It is also interesting to notice that the Malaysian households have a positive preference to their national vehicle’s brand, which are Proton and Perodua. This fact can be deduced from the model of type of vehicle, as well as the model of vehicle’s brand. The statistical result also shows that higher salary households tend to make more trips for any period of time.